Efectos de la teoría sociocultural de Vygotsky en el aprendizaje de una segunda lengua y aporte lingüístico (2017)
Objective. The present reflection article derives from a Diploma Course on Updating Teaching English Practices with Emphasis on Designing Learning Experiences, which took place at Universidad Industrial de Santander, Colombia. It is aimed at reflecting upon the key role of comprehensible input and social interactions between second language learners, teachers, peers and a meaningful learning environment. In addition, a revolutionary teaching model called SIOP for English learners will be described in terms of definition, justification and application to the classroom.Methodology. This paper is framed within a documentary research that, from a hermeneutic perspective, makes reference not only to the methodology, assignments and resources used for second language acquisition in a formal academic setting, but also to the suitable language input students should be encountered with to reach higher order thinking processes and develop outstanding communicative skills. The results of this conceptual analysis, focused on the Sociocultural Theory elaborated by the psychologist Lev Vygotsky, have allowed us to examine how a second language is learned successfully if teachers are able to manipulate input through effective scaffolding techniques which are thought to offer support to each student throughout the learning process until they can progressively get rid of it.Results. The impact of the Socio-cultural Theory by Vygotsky on second language acquisition leads us to suggest the SIOP as a new approach towards English teaching. This emphasizes the use of comprehensible input that is highly beyond students’ level of competence and multiple interactions at all levels throughout the lesson from the preparation and delivery to the assessment stage.